Speed control of a dc servomotor using analog controller / Anizah Hassan - Hassan, Anizah (1997)
The design of controllers or compensators of a control system using either the root locus or Bode plot techniques is based on the knowledge of the open-loop transfer function of the system. This thesis discusses the experimental determination of the transfer function of a de servomotor using frequency response techniques. An analog controller is then designed using the Bode plot technique to meet the desired specification. The designed of controller is then simulated using MATLAB. Through a simulation it is shown that the iead controller that is designed meet the desired specification.